The Implementation of Blended Synchronous and Asynchronous Online Language Learning during the Covid-19 Pandemic - Adhan Kholis (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
The Covid-19 Pandemic has disrupted interaction and communication between teachers and students in teaching and learning. Hence, online learning becomes recourse to reach students’ presence. Both are separated into divergent space and time. However, in practice, students get inconvenience in apprehending and receiving knowledge on screen given by teachers. Accordingly, certain manners have been led to solve and to simplify remote teaching by combining both synchronous and asynchronous learning modes. This study aimed to explore, to investigate, and to describe students’ perceptions and learning practices at implementation of online language learning using blended synchronous and asynchronous communication. Data obtained was from the observation, the interview, the students’ questionnaire derived from the Google Form, and the need analysis in the preliminary study toward higher students of Nahdlatul Ulama University of Yogyakarta majoring English Education Department. It was a case study research design. The descriptive and quantitative analysis was used to describe and to interpret the obtained data from respondents. The results showed that the students were more enthusiastic with the combination between synchronous and asynchronous learning modes than videoconference only. Furthermore, evidences represented the students were motivated with asynchronous tools such as WhatsApp, Google Docs, and Google Classroom with the reasons: easy to reach communication, cheap in costs, multifunction, and fast in responses. In acquiring clear interaction and a direct meeting, the live conference like Zoom and Google Meet became the right preferences for both teachers and the students.